PERLINDUNGAN PEKERJA MIGRAN INDONESIA/TENAGA KERJA INDONESIA OLEH PEMERINTAH DAERAH - Ihsan Dzuhur Hidayat (Universitas Islam Kadiri, 2021)
Protection of Migrant Workers is a shared responsibility, both from the Central government and local governments. This study aims to comprehensively analyze the Protection of Indonesian Migrant Workers by the Local Government. By using normative juridical approach methods as well as using interactive analysis models. It can be obtained from the discussion that the local government has responsibility and authority in carrying out the protection of migrant workers. According to the provisions of Law No. 23 of 2014 on Local Government, the District Government is obliged to carry out affairs in the field of employment. Employment affairs that are the authority of the district / city governmentinclude: Job Training and Labor Productivity, Labor Placement, Industrial Relations and Employment Supervision. Sub Division of Work Placement, District has authority in terms of Protection of Indonesian Migrant Workers both pre and after placement. The form of Protection of PrePlacement of Indonesian Migrant Workers in the region can be in the form of Supervision in terms of making employment agreements ranging from recruitment, education and training. Full-time forms of protection can be in the form of problem solving, defense of the fulfillment of the rights of indonesian migrant workers and physical and psychic recovery and management of return.